Migrants and Markets Perspectives from Economics and the Other Social Sciences - Kolb, Holger; Egbert, Henrik (IMISCOE Research, 2008)
The established academic discipline that is economics and migration research - as a growing sub-discipline that has inevitably transgressed its own academic bounds - have long treated each other with mutual indifference. While migration research has suffered from a normative overstretch, economics has often reduced its analytical scope to those areas that traditionally belong to the 'genuine' economic sphere. Migrants and Markets contains eleven case studies that aim to overcome this artificially imposed barrier between economics and migration research. This is accomplished by applying economic methods to migratory phenomena, using economic theories to explain migratory patterns and by approaching the structure and development of markets as integral to the shaping of stocks and flows of migrants. This title is available in the OAPEN Library - http://www.oapen.org.